ENHANCING STAFF-RESIDENT INTERACTIONS THROUGH A FRONTLINE STAFF QUALITY IMPROVEMENT INTERVENTION. (11th November 2018) - Hartmann, C; Palmer, J; Pimentel, C; Allen, R; Zhao, S; Wewiorski, N; Dillon, K; Snow, A
Abstract: For nursing home residents, positive interactions with staff and engagement in activity contribute meaningfully to quality of life. We sought to improve interactions between staff and residents, with the ultimate aim of enhancing resident engagement. We used an opportunistic, snowball sample of 6 Veterans Health Administration nursing homes (e.g., Community Living Centers—CLCs). Our staff-based behavior-change intervention involved staff using a set of evidence-based practices for implementing quality improvement: frontline huddles, rapid-cycle structured observations, a strengths-based approach, and the importance of brevity coupled with regularity. CLC staff facilitated the intervention, with some assistance from researchers. Research data comprised validated resident and staff surveys, researcher-conducted structured pre- and post-intervention observations, and semi-structured post-intervention staff interviews. 62 CLC residents and 308 staff members responded to the surveys. Researchers conducted 1, 490 discrete observations and 66 interviews. In generalized linear models using observation and survey data, intervention implementation was associated with increased staff-resident communication during the provision of direct care activities (β = 0.083, 95% CI: 0.04–0.126, adjusted P=.0012) and decreased negative staff interactions with residents (β = -0.035, 95% CI: -0.062 – -0.009, adjusted P=0.0288). In interviews, staff consistently credited the intervention with helping them (a) develop awareness of the importance of identifying opportunities for engagement and (b) improve the quality of their interactions with residents. Overall, the intervention proved feasible. The combination of rapid-cycle observations, huddles, and a focus on identified strengths influenced staff to make simple enhancements to their behaviors that improved staff-resident interactions and staff-assessed resident engagement.